Modeling a Service and Session Calculus with Hierarchical Graph Transformation - Bruni, Roberto; Corradini, Andrea; Montanari, Ugo (Electronic Communications of the EASST, 2010)
Graph transformation techniques have been applied successfully to themodelling of process calculi, for example for equipping them with atruly concurrent semantics. Recently, there has been an increasinginterest towards hierarchical structures both at the level ofgraph-based models, in order to represent explicitly the interplaybetween linking and containment (like in Milner's bigraphs), and atthe level of process calculi, in order to deal with several logicalnotions of scoping (ambients, sessions and transactions, amongothers). In this paper we show how to encode a sophisticated calculusof services and nested sessions by exploiting a suitable flavour ofhierarchical graphs. For the encoding of the processes of thiscalculus we benefit from a recently proposed algebra of graphs withnesting.